SUPER (a,d)-EDGE ANTIMAGIC TOTAL LABELING OF CONNECTED LAMPION GRAPH - Adawiyah, Robiatul; Dafik, D; Slamin, S (Kadikma, 2015)
Abstract. A G graph of order p and size q is called an (a,d)-edge antimagic total if there exist a bijection f: V(G)E(G) {1,2,…,p+q} such that the edge-weights, w(uv)=f(u)+f(v)+f(uv), uv E(G), form an arithmetic sequence with first term a and common difference d. Such a graph G is called super if the smallest possible labels appear on the vertices. In this paper we study super (a,d)-edge-antimagic total properties of connected £n,m by using deductive axiomatic and the pattern recognition method. The result shows that a connected Lampion graphs admit a super (a,d)-edge antimagic total  labeling for d = 0,1,2 for n It can be concluded that the result of this research has covered all the feasible d. Key Words: (a,d)-edge antimagic vertex labeling, super (a,d)-edge antimagic total labeling, Lampion Graph.